The Synthesis and Characterization of Zinc Oxide Nanorods and Nanoflower for Ethanol Gas Sensing Applications - Anbalagan, Kavita; Amerrudin, Amira Saryati (Enhanced Knowledge in Sciences and Technology, 2025)
Zinc oxide (ZnO) nanostructures, including nanorods and nanoflowers, were successfully synthesized using the hydrothermal method and subsequently coated onto substrates via spin coating. The morphological characteristics of the ZnO nanostructures were analysed using field emission scanning electron microscopy (FESEM), revealing well-defined nanorod and nanoflower morphologies. Optical properties were evaluated using UV-visible spectroscopy, confirming the material's high optical transparency and characteristic bandgap. The gas sensing performance of the ZnO nanostructures was tested in a custom-built setup under two temperature conditions: room temperature and 150°C. The nanoflower demonstrated a better sensitivity compared to the nanorod in both conditions. These findings provide valuable insights into the development of efficient and temperature-responsive gas sensors.